2022
DOI: 10.3390/su14063511
|View full text |Cite
|
Sign up to set email alerts
|

How Does New Infrastructure Investment Affect Economic Growth Quality? Empirical Evidence from China

Abstract: The current phase of the technological revolution and the accelerated rate of industrial change have encouraged the structural transformation of global infrastructure investment. This study aims to identify and evaluate the impact of new infrastructure investment on economic growth quality. This paper explains the theoretical mechanisms in terms of their effects on technological innovation, industrial structure, and productivity, using the three-dimensional analysis framework of economic growth conditions, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 71 publications
3
37
0
1
Order By: Relevance
“…Coefficient value obtained is positive 0.0788 indicates that if Infrastructure increase as much 1 km, economic growth will also increase as much 0.0788 percent. Previous studies in line with this finding are study by Novitasari et al, (2020) and Du et al, (2022) also found Infrastructure had significant and positive effect toward Economic Growth.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Coefficient value obtained is positive 0.0788 indicates that if Infrastructure increase as much 1 km, economic growth will also increase as much 0.0788 percent. Previous studies in line with this finding are study by Novitasari et al, (2020) and Du et al, (2022) also found Infrastructure had significant and positive effect toward Economic Growth.…”
Section: Resultssupporting
confidence: 77%
“…This research use multiple regression approach and found that infrastructure has significant and positive impacts on economic growth. Du et al, (2022) identified and evaluated the impact of new infrastructure investment on economic growth quality in China from 2004 to 2019. The findings demonstrate that new infrastructure investment has positive impact and significantly improve economic growth quality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent statistic has showed the new investment in the field of digital economy has contribute 67.9% to the economic growth [11]. Current investments in new infrastructure promote economic growth by fostering innovation in the digital sector, facilitating economic transformation, and improving productivity [12].…”
Section: New Infrastructure Investmentmentioning
confidence: 99%
“…Compared with traditional infrastructures, smart infrastructures are safer, more efficient, and more reliable. According to some experts, investment in NI construction will continue to rise in the future in order to promote improved infrastructure integration and smart cities [4]. To reduce the epidemic negative impact of the epidemic as soon as possible and promote the economy return to the normalcy, it is necessary to drive the economy by focusing on the NI [5].…”
Section: Introductionmentioning
confidence: 99%